Bioelectronic Nose Integration of Biotechnology and Nanotechnology - Park, Tai Hyun (Springer Netherlands : Imprint: Springer, 2014)
The "bioelectronic nose", the device which has a similar function to the human smell sensing system, can be realized by combining the olfactory cells or receptors with nanotechnology. In the last two decades, much has been learned about the smell sensing mechanism in biological systems. With knowledge about the biological olfactory system and the techniques for the expression of biological receptor proteins, we are able to utilize biological materials and systems to mimic the biological olfactory system. In addition to the advances in biological and biotechnological area, nanotechnology has progressed to a great degree. The bioelectronic nose is a good example of the integration of biotechnology and nanotechnology. This book describes basic biological sciences of the olfactory system, biotechnology for the production of olfactory biological elements, and nanotechnology for the development of various sensing devices. The purpose of this book is to provide the reader with a concept, basic sciences, fundamental technologies, applications, and perspectives of the bioelectronic nose.